Control of cowpea seedling mortality in Southern Nigeria - Williams, R.J. (1975)
In 12 field plantings in southern Nigeria during 1972 and 1973, four fungicides and four fungicide combinations were tested as seed dressings for the control of seedling mortality of cowpea. The greatest and most stable control was obtained with 1, 4-dichloro-2, 5-dimethoxybenzene (chloroneb) used as a dry seed dressing at rates of 2 and 4 g/kg seed. The combination of other fungicides with chloroneb, and the use of glycerol and kaolin to coat the seed with the fungicide, did not significantly improve its performance.